Major NTFP Items and their Marketing Potentials at Hazaribagh Forest Area in Jharkhand - a Case Study - Giri, T. K.; Mazumdar, A.; Santra, S. C. (Indian Forester, 2005)
The present study focuses on marketing aspects of selected NTFPs of commercial importance. Emphasis has been given to NTFP items collected by the villagers/NFMPC members in and around the forests under the JFM system. The collector of NTFPs gets a small fraction of surplus generated by produce sold in the market. The middlemen (the agents, traders and wholesellers) receive the maximum benefit from marketing of surplus NTFPs. There is an urgent need for policy intervention to ensure maximum returns to local people.